2017
DOI: 10.1177/1049909117715215
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and Misperceptions of Hospice and Palliative Care: A Population-Based Survey Study

Abstract: Most community-dwelling adults did not mention the major components of palliative and hospice care in their definitions, implying a low level of awareness of these services, and misinformation is common among community-dwelling adults. Palliative and hospice care education initiatives are needed to both increase awareness of and reduce misperceptions about these services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
117
2
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(138 citation statements)
references
References 29 publications
5
117
2
3
Order By: Relevance
“…Most responding physicians expressed concern that patients with ESLD would have negative emotional reactions to a PC referral, which may reveal an important barrier to PC referral for this patient population. The majority of physicians responded that patients with ESLD would associate a PC referral with the end of active disease‐specific therapy, abandonment by their care team, and imminent death, findings that have been corroborated in patient‐ and population‐based surveys . The perception that the term “palliative care” in and of itself triggers distress in patients has been reported previously by clinicians who care for patients with chronic illnesses .…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Most responding physicians expressed concern that patients with ESLD would have negative emotional reactions to a PC referral, which may reveal an important barrier to PC referral for this patient population. The majority of physicians responded that patients with ESLD would associate a PC referral with the end of active disease‐specific therapy, abandonment by their care team, and imminent death, findings that have been corroborated in patient‐ and population‐based surveys . The perception that the term “palliative care” in and of itself triggers distress in patients has been reported previously by clinicians who care for patients with chronic illnesses .…”
Section: Discussionsupporting
confidence: 57%
“…The majority of physicians responded that patients with ESLD would associate a PC referral with the end of active disease-specific therapy, abandonment by their care team, and imminent death, findings that have been corroborated in patient-and population-based surveys. (40)(41)(42) The perception that the term "palliative care" in and of itself triggers distress in patients has been reported previously by clinicians who care for patients with chronic illnesses. (15,16,22,23,43) To what extent patients with ESLD have a negative reaction to the term "palliative care" remains unclear, and further studies are warranted to specifically assess the perceptions of PC by patients with ESLD.…”
Section: Original Article | 867mentioning
confidence: 82%
“…Four reviews that were conducted in developed countries [41,[56][57][58] reported similar findings. Furthermore, a population-based study suggests that a low level of awareness and knowledge deficit common among adults are part of the challenges [59]. Another study linked insufficient knowledge and low level of awareness of patients, families, the public, and HCPs to PC services and their benefits [60] to these challenges, potentially contributing to delayed referrals of patients to PC services [61][62][63].…”
Section: Discussionmentioning
confidence: 99%
“…However, there are some similarities in challenges to PC provision. The main common obstacles to the provision of PC in both developed countries and LMICs include lack of a properly trained workforce [41,[56][57][58], fear among HCPs [106,107], lack of awareness about PC [59,60,[108][109][110], limited funding and lack of coordination amongst services [106]. However, in developing countries, factors affecting the provision of PC services to cancer patients further include lack of resources and inadequate physical infrastructure.…”
Section: Discussionmentioning
confidence: 99%
“…Alle Bürger sollten daher Basiswissen über Palliativversorgung (sprich Letzte Hilfe) lernen, um sich an der Versorgung schwerkranker und sterbender Menschen im Rahmen ihrer Möglichkeiten und Fähigkeiten beteiligen zu können [4]. Verschiedene Experten haben empfohlen, die Bevölkerung über Möglichkeiten der Palliativversorgung zu informieren [2][3][4][5], denn leider ist das Wissen von Bürgern über Sterben, Tod und Palliativversorgung unzureichend bis teilweise mangelhaft [6][7][8][9]. Die Idee von Letzte-Hilfe-Kursen wurde erstmals 2008 von Bollig beschrieben [4].…”
Section: Introductionunclassified